The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10350-007-9070-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Resection for Colorectal Cancer in Octogenarians: Results in a Decade

Abstract: Our experience confirms that laparoscopic colorectal cancer resection in selected octogenarians is safe and feasible. Aside from the obvious short-term benefits, the long-term oncologic outcomes are favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
3
36
1
2
Order By: Relevance
“…Previous studies have shown that colorectal surgery in elderly patients is generally well tolerated although pre-morbid cardiopulmonary conditions do predispose to higher morbidity and mortality rates as compared to younger patients [6,23]. Laparoscopic colorectal resection is fast becoming the gold standard of treatment for both malignant and benign colorectal lesions, with improved short-term and comparable long-term outcomes when compared to the open method [1,2,24]. Improved short-term outcomes after laparoscopy have been attributed to less post-operative pain, better pulmonary function and less stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that colorectal surgery in elderly patients is generally well tolerated although pre-morbid cardiopulmonary conditions do predispose to higher morbidity and mortality rates as compared to younger patients [6,23]. Laparoscopic colorectal resection is fast becoming the gold standard of treatment for both malignant and benign colorectal lesions, with improved short-term and comparable long-term outcomes when compared to the open method [1,2,24]. Improved short-term outcomes after laparoscopy have been attributed to less post-operative pain, better pulmonary function and less stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The elderly population in Singapore and the world is increasing, and with it, the incidence of colorectal cancer in this age group [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus conceivable that findings demonstrating the safety of a laparoscopic L Previous studies have evaluated outcomes after laparoscopic colorectal surgery among elderly patients [8][9][10][11][12][13][14][15]. Current data [16][17][18][19] pertaining to outcomes of laparoscopic colectomy (LC) for octogenarians are sparse. Only one matched-control study [18] compared outcomes after LC with those after open colectomy (OC), but it was disadvantaged by small numbers of patients in both groups.…”
mentioning
confidence: 95%